Kajian Ketahanan Terhadap Penyakit Busuk Daun (Phytophthora Infestans) pada Beberapa Galur Tomat - YASA, I NYOMAN DARMA; SUDIARTA, I PUTU; WIRYA, I GUSTI NGURAH ALIT SUSANTA; SUMIARTHA, KETUT; UTAMA, I MADE SUPARTHA; LUTHER, GREGORY C.; MARIYONO, JOKO (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol. 1, No. 2, Oktober 2012, 2012)
ABSTRACT Study of Resistance of Tomato Lines to Late Blight Disease ( Phytophthora Infestans) Indonesia is one of the tropical countries with high potential of horticulture, especially tomato. To produce high quality and quantity of tomato the one problem is plant diseases. The most cereus disease was reported as late blight, it is caused by Phytophthora infestans . P. infestans is commonly out break in high land area, with more than 1000 m acl.  The late blight can reduce the production of tomato or in some case make the loss of yield. To control the disease the farmers have been used the chemical fungicide. However the chemical fungicides have many negative impacts. Therefore to control the disease the one of possible way is using resistant plant. On the other hand the tomato has been planted in Indonesia has not resistance by the late blight. Base on that, the experiment to select some resistant plant was conducted. The experiment was done in high land area in Bukitcatu and Pancasari (Bedugul area 1200 m acl).  The experiment was conducted used 16 lines and 4 varieties. The15 lines were imported from AVRDC and 1 line and 3 varieties were come from IVEGRI and 1 variety is local used by farmer. The result shown the most resistance lines are AVTO 0922, AVTO 1122, and AVTO 1143 base on the disease incidence and severity observation. The AVTO 0922, AVTO 1122, and AVTO 1143 were significant difference with another lines and varieties. Keywords: Tomato lines, Phytophthora infestans, resistant plant
Keywords: Tomato lines; Phytophthora infestans; resistant plant